First confirmed diagnosis of Sheep-associated Malignant Catarrhal Fever in Bison in Argentina - Bratanich, A; Sanguinetti, H; Zenobi, C.; Balzano, R.; Debenedetti, R.; Rivolta, M.; Albareda, D.; Blanco Viera, J.; Venzano, A.; Capellino, F.; Funes, D.; Zacarias, S. (Brazilian Journal of Veterinary Pathology, 2012)
In Argentina, cases of malignant catarrhal fever (MCF) are suspected to have occurred according to macro and microscopic lesions. However, none has been corroborated by molecular tests. We describe here the first laboratory confirmed case of MCF in Argentina occurring in American bison confined in the Buenos Aires Zoo.